Cud w Mediolanie Vittoria De Siki na tle recepcji włoskiego neorealizmu w polskim piśmiennictwie filmowym do 1956 roku - Miller-Klejsa, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
After the end of the Second World War, cinema culture in the People’s Republic of Poland underwent a crucial transformation. One of the aspects of this change was the new movie import model: most international sources were replaced by films from the Communist bloc, principally the Soviet Union. Italian movies constituted an important exception. In addition, translations of works by C. Zavattini and U. Barbaro were published (the latter was even appointed a professor at the Film School in Lodz). However, some movies deemed neorealist were either not permitted by the censorship bodies (it banned several of Rossellini’s works) or appeared on Polish screens with a significant delay (which was the case of Umberto D.). The article focuses on the reception of the film Miracle in Milan (dir. Vittorio De Sica) in the Polish movie magazines and books published before 1956. The case of this film seems particularly interesting, as opinions on it have changed over the years (as has the assessment of the neorealist movement as a whole), and the film itself has provoked controversy. In the Stalinist period in Poland, critical opinions dominated, and Italian neorealism (and De Sica’s film) was accused of pessimism and losing sight of “great revolutionary perspectives”. The film’s fairy-tale formula and the “transcendental” themes present in the plot were also difficult to accept. This negative attitude changed during the Thaw, when neorealism became something of a positive example of progressive film aesthetics, an example to follow; the authorities then allowed neorealist films (including Miracle in Milan) to be framed in religious terms.